A Spatial Analysis on International Remittances, Food Consumption and Deprivation in Indonesia - Maria Elfani (JAS (Journal of ASEAN Studies), 2015)
This paper aims to illustrate how international remittances may relate to food consumption and deprivation in Indonesia. The idea is that international remittances may contribute to the reduction of poverty, and since food consumption is an element with which to measure poverty line, this paper intends to show whether international remittances are more likely to be received by poorer households–based on food consumption level in the households. Using Geographic Information Systems (GIS) and the data from the Indonesia Family Life Survey (IFLS4), this paper illustrates the mapping of international remittances and food consumption in some of Indonesia’s provinces. The spatial analysis shows correlation between international remittances and food consumption. International remittances tend to be received by households who have less spending on food. The geographical pattern shows that international remittances are more likely to be received by poorer households based on their food consumption. The result to some extent supports the view that international remittances might benefit the poor the most, particularly on tackling poverty, as poorer households are more likely to receive the remittances.